2021
DOI: 10.1038/s41386-021-01179-z
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin reuptake inhibitors and suicidal behaviour: a population-based cohort study

Abstract: There is concern that selective serotonin reuptake inhibitor (SSRI) treatment may increase the risk of suicide attempts or deaths, particularly among children and adolescents. However, debate remains regarding the nature of the relationship. Using nationwide Swedish registers, we identified all individuals aged 6–59 years with an incident SSRI dispensation (N = 538,577) from 2006 to 2013. To account for selection into treatment, we used a within-individual design to compare the risk of suicide attempts or deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 39 publications
3
28
0
2
Order By: Relevance
“…46 Many studies have been conducted on the effect of antidepressants in treating depression and preventing suicide, and completely different results have been extracted. Some studies have reported a positive effect, [47][48][49] and others have said an adverse effect or lack of effectiveness of these drugs. [50][51][52] One of the reasons for the non-use of antidepressants by the participants may be the belief that these drugs cause dependence and addiction and should be taken for a lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…46 Many studies have been conducted on the effect of antidepressants in treating depression and preventing suicide, and completely different results have been extracted. Some studies have reported a positive effect, [47][48][49] and others have said an adverse effect or lack of effectiveness of these drugs. [50][51][52] One of the reasons for the non-use of antidepressants by the participants may be the belief that these drugs cause dependence and addiction and should be taken for a lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…Seksuell dysfunksjon er vanlig hos både kvinner og menn (4), og høye doser citalopram og escitalopram er kontraindisert grunnet fare for arytmier (5). Det er også bekymring for en initial økning i selvmordsforsøk (3), selv om noen studier indikerer det motsa e (6).…”
Section: H Ov E D F U N Nunclassified
“…Ein besonderes Augenmerk muss auf die Diskussion bezüglich eines möglicherweise erhöhten Suizidrisikos unter der Einnahme von SSRI gelegt werden. Neuere Studien und Metaanalysen weisen insgesamt nicht eindeutig auf ein erhöhtes Suizidrisiko hin [15], jedoch ist weiterhin unbedingt eine Aufklärung über diesen Umstand sowie die Besprechung eines Notfallplans mit Patienten notwendig.…”
Section: Vorsichtunclassified